Pelayanan Perizinan Melalui Sistem Online Single Submission Risk Based Approach (OSS-RBA) Pada Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Dan Tenaga Kerja Kabupaten Kuantan Singingi - Milta, Chyndi Berliana; Mayarni, Mayarni (Journal of Research and Development on Public Policy, 2023)
It is known that there are still some deficiencies, namely the limited ability or understanding of users in operating electronic service systems, which in this case the OSS-RBA program is known as the digital divide. Some of these deficiencies in the DPMPTSPTK of Kuantan Singingi Regency were the presence of complaints from the public about the difficulty in understanding licensing processing with changes to the permit application process using the system. The licensing process takes quite a long time because it depends on the network of officers working. The limited ability of these business actors makes them continue to visit the Office of Investment and One-Stop Integrated Services (DPMPTSP) of Kuantan Singingi Regency to process account registration and issue business licenses. The large number of business actors who come to the DPMPTSPTK results in the service process taking quite a long time, this is because the internet network at the DPMPTSPTK agency is still joined to the Regent's Office and the IT is always problematic so the internet connection is sometimes slow and the internet connection is lost. This is an obstacle in the data entry process for business actors, which hinders and slows down the assistance services for OSS-RBA operators at the DPMPTSPTK of Kuantan Singingi Regency for business actors. With the need for commitment and willingness from the service provider to be able to help and be open to input given by service recipients in obtaining business licensing. Several licensing service agencies in Indonesia have started to create a joint consensus in the licensing service process which is managed by the public (Adianto et al., 2017). Besides that, there is a lack of training from the DPMPTSPTK service for human resources in implementing the OSS-RBA system. In addition, it is recognized that currently the electronic licensing that has been implemented by the DPMPTSPTK of Kuantan Singingi Regency is not well known or understood by business actors due to the uneven distribution of direct socialization regarding how to use OSS-RBA services online to every region in the Regency. Kuantan Singingi.